Strain Evolution and Instability of an Anticyclonic Eddy From a Laboratory Experiment - Han, Guoqing; Dong, Changming; Yang, Jingsong; Sommeria, Joel; Stegner, Alexandre; Caldeira, Rui M. A. (Frontiers in Marine Science, 2021)
Using the 13-m diameter LEGI-Coriolis rotating platform, the evolution processes of a generated anticyclonic eddy throughout its lifecycle are analyzed. Experimental results have shown that the eddy lasted for approximately 3T0, where T0 is the rotating period of 90 s. After T = 0.3T0, the eddy enters its mature phase, whereby following this event, eddy intensity slowly decreases from its maximum rotation speed. By T = 2.6T0, the eddy enters a stage of rapid weakening. In its decay period, two underlying mechanisms for this decay have been identified as inertial instability and eddy-eddy interactions.